Guatemala : Third Review Under the Stand-By Arrangement; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guatemala. (IMF Staff Country Reports; Country Report ;, 2010)
The Guatemalan economy is recovering faster than anticipated during the previous program review. The economic outlook has improved since the second program review. The fiscal deficit in 2010 will decline somewhat. There was agreement that a comprehensive tax reform remains the key medium-term challenge. There was agreement that monetary policy should remain vigilant. There has been progress in advancing financial sector reforms, but key elements of the reform agenda are pending. The near-term outlook has improved since the second program review, and downside risks have declined further.